Corporate Social Responsibility: Contradictions, Abuse of Ethics, and the Role of the Idea - Guczalska, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The author posits that corporate social responsibility (CSR), in the narrow definition of the term, is not so much a positive idea that leads towards a better future, sustainable development, and sustainable economy, but a tool in the struggle for the right to manage a corporation; the politicisation of economy; and a way to camouflage activities which do not pursue noble ethical ideas but rather financial profit. The article presents arguments for the thesis that CSR, understood as an ideology used by corporate boards, has contributed to a crisis of corporate order. This is because, as a strategy or model of management, CSR has shaped certain relations between owners and shareholders, which have contributed to the weakness of shareholder supervision and control. The author opposes the too-ready idealisation of the idea of CSR, abuse of ethics (such as moral hazard or the bailout), and the theoretical inconsistency of Kantian capitalism. The cases analysed here highlight the fact that upper management is not held accountable for the consequences of poor decision-making and mistakes, which is inconsistent with the notion of CSR. The shortcomings of CSR are brought to light through the juxtaposition of Kantian capitalism, i.e. Robert E. Freeman’s theory of stakeholders, with Milton Friedman’s model of shareholder capitalism.